O termo KABOD no livro de Ezequiel - Kunz, Marivete Zanoni (2006)
This essay is an analysis of the kabod concept in the book of Ezekiel. The same word is also used in other parts of the Old Testament. Therefore the research will also make a brief survey of this use. In the first chapter, an examination of the use of the word in other parts of the Old Testament will be made, as well as a general conceptualization. In the second chapter, aspects of the book of Ezekiel related to the time context, such as a historical, political, social and religious situation. Eventually, in the third chapter, the study will be completely on some book excerpts. This study will happen from their exegesis. The structure will offer a general description of the excerpt literary context, which will be studied in detail, followed by its detailed study, emphasizing a consideration about kabod in the section.